Design of Asset Collection Information System Based on Website - Dwi Edi Sadharma (Lembaga Komunitas Informasi Teknologi Aceh (KITA), 2021)
The Asset Management Information System is one of the data processing activities at the Aceh Plantation Office, to obtain information about assets that is more targeted and easy to obtain. In writing this thesis, the author only discusses the problem of designing a web-based Asset Management Information System at the Aceh Plantation Service. The research objective was to identify and design a web-based Asset Management Information System at the Aceh Plantation Service and the Asset Management Information System Design using PHP and MySQL. The collection of data needed in writing this thesis is obtained by two methods, namely literature study related to library books and other scientific works, field studies by conducting interviews, and direct observation of objects related to this thesis. Asset Management Information System is carried out by one of the administrative staff in the field of administration to record and input asset data. From the results of the study, it can be concluded that the Asset Management Information System at the Aceh Plantation Office has followed procedures and uses a computer with HTML, CSS, JQuery, JSON, PHP, and MySQL programming languages as the database.